MANAGEMENT OF DIABETES IN RAMADAN - Badshah, Aliena; Haider, Iqbal; Humayun, Mohammad (Journal of Ayub Medical College Abbottabad, 2018)
Ramadan, the ninth month of Islamic calendar brings alongwith it a sense of responsibility to fast among the Muslim adult population. Though patients with chronic illnesses like Diabetes mellitus are exempted from fasting during the month if their health does not allow, they still wish to fast. This creates a challenge for the health care professionals to enable the patients with Diabetes mellitus to fast safely, without developing complications like hypoglycemia, hyperglycemia, ketoacidosis and thrombosis. This article has reviewed multiple articles published over last two decades to develop a consensus plan regarding management of Diabetes mellitus in Ramadan. Insulin sensitizers are a better option than drugs increasing secretion of insulin. Type 2 Diabetic patients can fast much safely as compare to Type 1 Diabetics. Keywords: Diabetes mellitus; Ramadan; Fasting; Hypoglycaemia; Hyperglycaemia; Ketoacidosis; Insulin